Genesis : A Pentecostal Commentary - Brian, Peterson, (Biblical Studies, Ancient Near East and Early Christianity E-Books Online, Collection 2022., 2022)
The Mediality of Sugar probes the potential of reading sugar as a mediator across some of the disciplinary distinctions in early twenty-first century research in the arts, literature, architecture, and popular culture. Selected artistic practices and material cultures of sugar across Europe and the Americas from the sixteenth to the twenty-first century are investigated and connected to the transcontinental and transoceanic history of the sugar plants cane and beet, their botanical and cultural dissemination, and global sugar capital and trade under colonialism and in decoloniality. The collection contributes to the vision of a Transnational and Postdisciplinary Sugar Studies.